2016
DOI: 10.1590/bjpt-rbf.2014.0169
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diaphragm stretching on posterior chain muscle kinematics and rib cage and abdominal excursion: a randomized controlled trial

Abstract: BackgroundFew studies have explored the effects of stretching techniques on diaphragm and spine kinematics.ObjectiveTo determine whether the application of diaphragm stretching resulted in changes in posterior chain muscle kinematics and ribcage and abdominal excursion in healthy subjects.MethodEighty healthy adults were included in this randomized clinical trial. Participants were randomized into two groups: the experimental group, which received a diaphragmatic stretching technique, or the placebo group, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
1
13
0
1
Order By: Relevance
“…Also, since this questionnaire items assess the pain Improved chest expansion was observed after treatment in both groups. Improved xiphoid level chest expansion after diaphragm myofascial release is consistent with the ndings of previous studies (14,15,26) and could be partially related to diaphragm attachments. Muscular bers of the diaphragm are attached to the sternum (xiphoid process), lower 6 ribs, and lumbar vertebrae (the L1, L2, and L3 vertebrae and arcuate ligaments) (12).…”
Section: Discussionsupporting
confidence: 91%
“…Also, since this questionnaire items assess the pain Improved chest expansion was observed after treatment in both groups. Improved xiphoid level chest expansion after diaphragm myofascial release is consistent with the ndings of previous studies (14,15,26) and could be partially related to diaphragm attachments. Muscular bers of the diaphragm are attached to the sternum (xiphoid process), lower 6 ribs, and lumbar vertebrae (the L1, L2, and L3 vertebrae and arcuate ligaments) (12).…”
Section: Discussionsupporting
confidence: 91%
“…Astudy done by Noll et al (2008) has reported a positive result on pulmonary function after the patients underwent the Redoming of Diaphragm technique (Noll et al, 2008). In a study done by González-Álvarez et al (2016) the diaphragm stretch technique was performed on healthy subjects which has shown an improvement in the posterior chain kinematics (González-Álvarez et al, 2016). Bhilpawar and Arora (2013) conducted a study with a combination of manual Therapy including the diaphragmatic stretch technique or redoming of diaphragm technique which showed a signi icant improvement in chest expansion and improvement in respiratory rate (Bhilpawar and Arora, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies explored the effect of the diaphragmatic release technique in subjects with COPD 16,32 and in subjects who were healthy and sedentary. 14,15,18,33,34 Rocha et al 16 analyzed the effect of 6 treatments with the diaphragmatic release technique versus a sham treatment in subjects with COPD on nonconsecutive days over the course of 2 weeks. Their results showed significant improvements in diaphragmatic mobility, inspiratory capacity, and exercise capacity.…”
Section: Discussionmentioning
confidence: 99%